PENERAPAN METODE ROLE PLAYING TERHADAP HASIL BELAJAR SISWA PADA MATERI JUAL BELI DALAM PEMBELAJARAN IPAS KELAS IV SDN 1 LAMBHEU ACEH BESAR - Mahirunnisa; Nurmasyitah; Tursinawati (STKIP Subang, 2026)
The low learning outcomes of students in IPAS learning on buying and selling material are indicated by scores that are still below the Minimum Learning Achievement Criteria (KKTP). This condition is influenced by teacher-centered learning, limited variation in instructional methods, and students’ low participation in discussions and peer interactions. As a result, students tend to be passive and lack confidence, making the learning process less meaningful. This study aims to determine the implementation of the Role Playing method and its impact on students’ learning outcomes in IPAS learning on buying and selling material in the fourth grade of SDN 1 Lambheu, Aceh Besar. This study employed a descriptive qualitative approach. The research subjects consisted of 25 fourth-grade students and one IPAS teacher. Data were collected through observation and learning outcome tests. Data analysis was conducted qualitatively through data reduction, data display, and conclusion drawing, supported by the calculation of mean scores and the percentage of learning mastery. The results showed that the implementation of the Role Playing method improved students’ active participation during the learning process, particularly in role-playing and discussion activities. Students became more enthusiastic, confident, and cooperative in group work. Furthermore, students’ learning outcomes significantly improved, with an average score of 82.4 and a mastery percentage of 84%, exceeding the established KKTP. Therefore, the Role Playing method can be considered an effective alternative instructional strategy to enhance students’ engagement and learning outcomes in buying and selling material.